THE IMPLEMENTATION OF CHARACTER EDUCATION IN PREPARING THE STUDENTS TO FACE INDUSTRIAL REVOLUTION 4.0 –A RESEARCH OF ENGLISH FOR ENGINEERING IN DARMA AGUNG UNIVERSITY - Corry Ester Margaret Siagian (LP2M Universitas Muslim Nusantara Al Washliyah, 2020)
This article is about the implementation of how the lecturer can contribute as an agent of transferring culture and knowledge in preparing the students to face the Industrial Revolution 4.0 by doing the Character Education to the students of Mechanical Engineering in learning English for Engineering Students. This study is done in faculty of Engineering in the University of Darma Agung, Medan. It is a qualitative research and used documentation and questioner technique in collecting the data needed. The lecturer implements character education by being a role model, building a targeted behavior culture, giving punishment and appraisal and using the appropriate teaching materials and method based on the needs of the students and the targeted workplace.